Research status and trends of the diabetic cardiomyopathy in the past 10 years (2012–2021): A bibliometric analysis - Wang, Sicheng; Tian, Chuanxi; Gao, Zezheng; Zhang, Boxun; Zhao, Linhua (Frontiers in Cardiovascular Medicine, 2022)
Background Diabetic cardiomyopathy is one of the most life-threatening diabetic complications. However, the previous studies only discuss a particular aspect or characteristic of DCM, the current state and trends were explored by limited research. We aimed to perform a systemically bibliometric study of DCM research progress status in the past decade, visualize the internal conceptual structure and potential associations, and further explore the prospective study trends. Methods Articles related to DCM published from January 2012 to December 2021 were collected in the Web of Science core collection (WoSCC) database on June 24, 2022. We exported all bibliographic records, including titles, abstracts, keywords, authorship, institutions, addresses, publishing sources, references, citation times, and year of publication. In addition, the journal Impact Factor and Hirsch index were obtained from the Journal Citation Report. We conducted the data screening, statistical analysis, and visualization via the Bibliometrix R package. VOS viewer software was employed to generate the collaboration network map among countries and institutions for better performance in visualization. Results In total, 1887 original research articles from 2012 to 2021 were identified. The number of annual publications rapidly increased from 107 to 278, and a drastic increase in citation times was observed in 2017-2019. As for global contributions, the USA was the most influential country with the highest international collaboration, while China was the most productive country. Professor Cai Lu was the most prolific author. Shandong University published the most articles. Cardiovascular Diabetology journal released the most DCM-related articles. “Metabolic Stress-induced Activation of FoxO1 Triggers Diabetic Cardiomyopathy in Mice” Battiprolu PK et al., J Clin Invest, 2012. was the most top-cited article regarding local citations. The top three keywords in terms of frequency were apoptosis, oxidative stress, and fibrosis. The analysis of future topic trends indicated that “Forkhead box protein O1”, “Heart failure with preserved ejection fraction”, “Dapagliflozin”, “Thioredoxin”, “Mitochondria dysfunction”, “Glucose”, “Pyroptosis”, “Cardiac fibroblast” and “Long non-coding RNA” could be promising hotspots. Conclusions This study provides meaningful insights into DCM, which is expected to assist cardiologists and endocrinologists in exploring frontiers and future research directions in the domain through a refined and concise summary.